Protein Intake During Early Complementary Feeding Affects the Gut Microbiota in U.S. Formula-fed Infants (FS04-03-19). (13th June 2019) - Tang, Minghua; Frank, Daniel; Hendricks, Audrey; Ir, Diana; Krebs, Nancy
Abstract: Objectives: Distinctive growth patterns were observed in formula-fed infants consuming a meat- or dairy-based complementary diet. The gut microbiota and its metabolites are characterized and compared in infants consuming these two common protein-rich foods. Methods: Healthy, term, formula-fed infants were recruited from metro Denver area, matched by sex and race/ethnicity, and randomized to a meat or a dairy complementary food group from 5 to 12 months of age. Meat- and dairy-based complementary foods and the same infant formula were provided. Total protein intake during the 7-month intervention was ∼3 g/kg/d for both groups. Intakes of infant formula, cereal, fruits, and vegetables were ad libitum. 16S rRNA sequencing and fecal metabolomics were conducted on stool samples collected at 5, 10 and 12 months. Results: Stool samples were collected from 59 infants (Meat n = 29; Dairy n = 30). Alpha diversity increased over time in the meat group ( P = 0.007), not dairy ( P = 0.17). Firmicutes was the most abundant phylum for both groups at all time points and Proteobacteria decreased abundance from 5 (10 ± 4%) to 12 months (5 ± 3%) in both groups. At Genus level, Bifidobacterium significantly decreased (21% to 16%, P = 0.001) and Faecalibacterium significantly increased (0.5 to 3.5%, P = 0.0006) over time in both groups, as expected for this age range and with the transition to complementary feeding. A significant group-by-time interaction was observed for Ruminococcus ( P = 0.001) and Roseburia ( P = 0.002), with increased abundances only in the meat group, not dairy. The abundance of Ruminococcus at 12 months was positively associated with length-for-age Z scores in the dairy group ( P = 0.007, R 2 = 31%). Both Ruminococcus and Roseburia are potential short-chain fatty acid producers and we saw a significant increase of butyrate and acetate productions in the meat group over time. Conclusions: Types of protein-rich foods during complementary feeding were associated with the gut microbial composition and metabolites in formula-fed infants. These changes of the gut microbiota may be associated with the different infant growth patterns. Funding Sources: NIH (NIDDK), NIH/NCATS Colorado CTSA and (alphabetically) Abbott Nutrition, the American Heart Association, the Beef Checkoff through the National Cattlemen's Beef Association, Leprino foods, the National Pork Board.